Tuberculosis and Pregnancy: clinicopathologic Interactions - Barreto, Luis (2015)
OBJECTIVES: To establish the influence of tuberculosis on gestation, birth and newborn. To determine the reactivation factors and the course of tuberculosis during gestation. To estimate the influence of nutritional factor of tuberculous pregnant women on adverse perinatal outcome. DESIGN: Descriptive retrospective study of cases and controls, revising the clinical histories of patients attended at the Gynecologic Obstetrics service of Edgardo Rebagliati Martins Hospital during the years 1990-1995. MATERIAL: Group cases, were 31 pregnants with diagnosis of tuberculosis and the control group 31 pregnants without diagnosis of tuberculosis. RESULTS: Ninety percent of tuberculosis reactivated during gestation. A great percentage of patients with tuberculosis had history of tuberculosis (p < 0,048). In these patients specific treatment for tuberculosis prior to gestation was irregular and/or of short duration, in distinction from the pregnant group that did not show TBC during pregnancy, but who had history of the disease, and received a proper or complete treatment (p< 0,046 and p <0,049 respectively). Significant deferences between tuberculous and nontuberculous patients were not found in relation to adverse perinatal outcome: abortion (3% vs 0%), low birth weight (37% vs 33%), intrauterine growth retardation (27% vs 67%) and small for gestational age (18% vs 0%) (p > 0,05). On the other hand the adverse perinatal outcome are related to had nutritional condition, low weight before pregnancy, low weight increase p > 0,05. CONCLUSION: In our study, gestation itself is not a risk factor for reactivation of tuberculosis. Reactivation is associated with history of tuberculosis with irregular and short duration treatment. Tuberculosis did not alter perinatal outcome in our study. Mothers with low weight prior to pregnancy and/or little weight gain during gestation, have greater incidence of children with low birth weight, intrauterine growth retardation and small for gestational age.